Link between the stress-recovery balance and mindfulness in young elite BMX riders - Sondt, N.; Bernier, M.; Kermarrec, G.; Vacher, P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction The stress-recovery balance refers to the quality of adjustment of recovery strategies that one mobilizes according to his or her stress states (Kellmann, 2010). Maintaining this balance plays an important part for the athletes and the coaches to reach an optimal performance. Currently, the scientific literature tries to develop the knowledge about psychological strategies of recovery among which, mindfulness has captured in interest (Blevins et al., 2021). From a biopsychosocial perspective, the aim of the study was to explore the links between mindfulness and the stress-recovery balance.